Psychiatric co morbidities in ESRD Patients Recently Placed on Haemodialysis : A Prospective Observational Study from a Tertiary Care Hospital - Iqbal, Sarwar; Talukder, Umme Salma; Chowdhury, Tufayel Ahmed; Billah, Md Mostarshid; Anana, Mehruba Alam; Rahim, Muhammad Abdur; Samad, Tabassum; Haque, Wasim Md Mohosinul; Faruq, Mohammad Omar (Bangladesh Critical Care Journal, 2016)
Background: Psychiatric co-morbidity especially anxiety and depression are common in patients who are recently placed on dialysis, but very little research has been done on this subject. Mental illness results in increased non-compliance in accepting dialysis and this results in increased mortality in End Stage Renal Disease (ESRD) patients. Methodology: This cross- sectional study was done on ESRD patients newly diagnosed and initiated hemodialysis in the department of Nephrology of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka, Bangladesh with informed written consent and maintaining privacy. Diagnostic and Statistical Manual of Mental Disorders (DSM-V) was used for diagnosis of psychiatric disorders. Patients on maintenance hemodialysis for more than 1 month and patients on Chronic Ambulatory Peritoneal Dialysis were excluded in this study. Results: There were total 83 patients out of whom there were 50 (62.2%) males and 33(39.38%) females. Mean age of study patients was 56.8±9.96 years. Bulk of the patients was clinically depressed (68.7%), followed by anxiety disorder (13.3%) rest were acute stress disorder, adjustment disorder and one case of psychosis. 8.4% participants denied any symptoms. Conclusion: Significant psychiatric co-morbidities developed in newly diagnosed ESRD subjects when they were prescribed hemodialysis. This study showed majority of the patients with renal failure on initiating hemodialysis who develop different psychiatric problems that need prompt diagnosis and appropriate treatment. These interventions will improve the quality of life of ESRD patients Bangladesh Crit Care J March 2016; 4 (1): 28-32